A Self‐Powered Piezo‐Bioelectric Device Regulates Tendon Repair‐Associated Signaling Pathways through Modulation of Mechanosensitive Ion Channels. Issue 40 (23rd August 2021) - Fernandez‐Yague, Marc A.; Trotier, Alexandre; Demir, Secil; Abbah, Sunny Akogwu; Larrañaga, Aitor; Thirumaran, Arun; Stapleton, Aimee; Tofail, Syed A. M.; Palma, Matteo; Kilcoyne, Michelle; Pandit, Abhay; Biggs, Manus J.
Abstract: Tendon disease constitutes an unmet clinical need and remains a critical challenge in the field of orthopaedic surgery. Innovative solutions are required to overcome the limitations of current tendon grafting approaches, and bioelectronic therapies show promise in treating musculoskeletal diseases, accelerating functional recovery through the activation of tissue regeneration‐specific signaling pathways. Self‐powered bioelectronic devices, particularly piezoelectric materials, represent a paradigm shift in biomedicine, negating the need for battery or external powering and complementing existing mechanotherapy to accelerate the repair processes. Here, the dynamic response of tendon cells to a piezoelectric collagen‐analogue scaffold comprised of aligned nanoscale fibers made of the ferroelectric material poly(vinylidene fluoride‐ co ‐trifluoroethylene) is shown. It is demonstrated that motion‐powered electromechanical stimulation of tendon tissue through piezo‐bioelectric device results in ion channel modulation in vitro and regulates specific tissue regeneration signaling pathways. Finally, the potential of the piezo‐bioelectronic device in modulating the progression of tendinopathy‐associated processes in vivo, using a rat Achilles acute injury model is shown. This study indicates that electromechanical stimulation regulates mechanosensitive ion channel sensitivity and promotes tendon‐specific over non‐tenogenic tissue repair processes. Abstract : Under physiological conditions, ion‐channels activity limit membrane depolarization and regulate ion concentration‐dependent signaling cascades. In response to injury or mechanical loading, the activity and expression of the ion‐channels increases, and unspecific tissue‐repair signaling pathways activate, resulting in ectopic calcification. By modulating the mechanosensitive ion‐channels' expression, electromechanical stimulation regulates specific signaling pathways activation to promote tendon over bone formation processes.